Propuesta de flotación para la separación del residuo PVC/poliéster en Croydon Colombia S.A. (2018)
The objective of this project is the development of a flotation proposal for the separation of PVC / polyester waste in Croydon Colombia S.A. taking into account that currently this waste is not used 100%. This proposal seeks to achieve an advantage of this waste by means of flotation, in order to improve the process of use of the company and to recirculate more PVC recovered to the fuel transfer. For the development of this proposal, the appropriate flotation solvent for the separation of the PVC / polyester waste was selected, for this a series of stages were carried out to define specific characteristics of the waste and the reagents to carry out the flotation process. Once these stages and parameters were defined, experimentation was carried out with both flotation reagents, which were Nonil phenol 10 moles and Tensafor MV-P, carrying out 16 tests in total.